Are fluent letter dyads really fluent? An update on objective and subjective motor fluency in an Italian student population - Mara Stockner; Giuliana Mazzoni; Francesco Ianì (Cognitive Research)
Abstract “Motor fluency” refers to the ease with which an action can be performed and several studies have shown how it can modulate various cognitive processes, such as memory and decision making. To investigate these implications of motor fluency, typing-based paradigms have been proven to be useful. In this literature, based on pioneering works that analysed inter-keystroke intervals (IKIs, the time that elapses between two keystrokes), several studies have assumed that letter dyads typed with different hands are more fluent than dyads typed with the same hand. However, to date, there is no literature analysing subjectively perceived typing fluency, i.e. the feeling of fluency experienced by typists. Moreover, this classical conceptualization has not been updated in the last decade. This raises the question of whether this distinction is also reflected in the subjective feeling of fluency, and whether it is still valid in today’s generation of everyday typists. Thus, we investigated the validity of dyad fluency classification by measuring both objective and subjective typing fluency in two samples of university students. The objective measure included both the response times required to type the entire dyads (Experiment 1) as well as reaction times from stimulus presentation to first keypress alongside IKIs (Experiment 2). Overall, we found consistent results that both objective and subjective measures follow the opposite trend compared to classical assumptions: same-hand dyads are (perceived) more fluent than different-hands dyads. Our results have important methodological implications for future research on typing-related motor fluency.